2021
DOI: 10.1021/acs.analchem.1c01461
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishment of Glycan Isomers by Trapped Ion Mobility Spectrometry

Abstract: The in-depth study of glycan has drawn large research interests since it is one of the main biopolymers on the earth with a variety of biological functions. However, the distinguishment of glycans is still difficult due to the similarity of the monosaccharide building block, the anomer, and the linkage of glycosidic bonds. In this study, four novel and representative copper-bound diastereoisomeric complex ions were simultaneously detected in a single measurement by trapped ion mobility mass spectrometry, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Previous literature on disaccharide IMS separations has postulated that the presence of multiple peaks (as seen for maltose in Figures A–E) could either be caused by their α/β anomers at the reducing end or multiple cation attachment site conformations. , Solution-phase NMR-based studies found that the α and β anomers for d -glucose exist in an ∼40:60 ratio (36:64 was the calculated ratio). In solution phase, the α/β anomers exist in an equilibrium with one another and interconvert (i.e., undergoing mutarotation) through an open-ring intermediate structure. However, in the gas phase they exist as two distinct, non-interconverting, structures as has been demonstrated with previous SLIM IMS–MS-based separations . From the cIMS–MS separations of maltose (which has d -glucose at its reducing end) as its [M + Li] + , [M + Na] + , and [M + K] + adducts, the two observed peaks are all calculated to be approximately in the same 40:60 ratio as the α/β anomers of d -glucose as calculated by NMR (see the Supporting Information for experimentally calculated α/β anomer ratios).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous literature on disaccharide IMS separations has postulated that the presence of multiple peaks (as seen for maltose in Figures A–E) could either be caused by their α/β anomers at the reducing end or multiple cation attachment site conformations. , Solution-phase NMR-based studies found that the α and β anomers for d -glucose exist in an ∼40:60 ratio (36:64 was the calculated ratio). In solution phase, the α/β anomers exist in an equilibrium with one another and interconvert (i.e., undergoing mutarotation) through an open-ring intermediate structure. However, in the gas phase they exist as two distinct, non-interconverting, structures as has been demonstrated with previous SLIM IMS–MS-based separations . From the cIMS–MS separations of maltose (which has d -glucose at its reducing end) as its [M + Li] + , [M + Na] + , and [M + K] + adducts, the two observed peaks are all calculated to be approximately in the same 40:60 ratio as the α/β anomers of d -glucose as calculated by NMR (see the Supporting Information for experimentally calculated α/β anomer ratios).…”
Section: Resultsmentioning
confidence: 96%
“…In an effort to better understand the source of multiple peaks for a single, pure isomer in carbohydrate IMS–MS separations, as has been underscored in previous literature, , initially, the behavior of two disaccharide linkage isomers (maltose; Glc­(α1,4)­Glc and cellobiose; Glc­(β1,4)­Glc) as a function of their singly lithiated, sodiated, potassiated, rubidiated, and cesiated adducts (see Table for their m / z values and Figure for their structures) was studied. After 15 m of cIMS separation (Figure ), two IMS peaks (although not well resolved in all cases) were observed for maltose for each of the metal adducts assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion mobility (IM) is a well-established analytical technique to characterize the structure of chemical compounds, , mainly due to the intrinsic capacity to recognize isomers and provide collision cross section (CCS) values that give an insight into structure partitioning. In recent years, different IM technologies have been developed and interfaced with MS, such as traveling wave drift cells (TWIMS), drift tube ion mobility spectrometry (DTIMS), differential mobility spectrometry (DMS), field asymmetric ion mobility spectrometry (FAIMS/DMS), trapped ion mobility spectrometry (TIMS), , and aspiration ion mobility spectrometry (AIMS) . Among these, TIMS is a powerful IM technique introduced by Park and co-workers in 2011 whose proof-of-concept was based on the work of Loboda .…”
mentioning
confidence: 99%
“…TIMS has proven to be a highly versatile alternative to drift tube ion migration, where ions are accumulated and analyzed inside the ion funnel . The introduction of TIMS and its integration with MS analyzers is a promising advancement for gas-phase ion analysis, which may overcome the major limitations associated with MS and chromatographic methods. , However, the direct separation and detection of cis/trans and d -/ l -enantiomers in TIMS-MS are limited because of they have the same mass–charge ratio ( m / z ) and very similar structure. In conclusion, the direct simultaneous separation of enantiomeric substances with cis-/trans-/ d -/ l chirality is still an intricate challenge.…”
mentioning
confidence: 99%